A Dual-Label Time-Resolved Fluorescence Immunoassay for the Simultaneous Determination of Cardiac Troponin T and Myoglobin. (April 2017) - Wang, Ling; Xu, Mujuan; Huang, Ruolan; Chang, Xiao; Chen, Cuicui; Li, Laiqing; Zhang, Zhong; Han, Yue
The aim of this study was to establish a dual-label time-resolved fluorescence immunoassay (TRFIA) for the simultaneous determination of cardiac troponin T (cTnT) and myoglobin (MYO) for the early diagnosis of acute myocardial infarction. The sandwich immunoassay was used to detect the concentration of cTnT and MYO in serum. cTnT and MYO in serum were captured by anti-cTnT and anti-MYO antibodies immobilized on microtiter wells and then banded together with another anti-cTnT and anti-MYO labeled with europium(III) Sm 3+ and samarium(III) Eu 3+ chelates, followed by fluorescence measurement using time-resolved fluorometry. The performance of this TRFIA was evaluated using the clinical serum and compared with the commercial assays. The linear correlation coefficients ( R 2 ) of the cTnT and MYO standard curves were 0.9993 and 0.9995, respectively. The sensitivity for cTnT detection was 2.21 pg/mL (linear dynamic range was 3.24–963.71 pg/mL), and the average recovery was 100.57%. The sensitivity for MYO detection was 3.24 ng/mL (linear dynamic range was 4.95–976.85 ng/mL), and the average recovery was 99.79%. High correlation coefficients ( R 2 ) were obtained between the commercial assays and dual-label TRFIA ( R 2 = 0.999). The present dual-label TRFIA has high sensitivity, specificity, and accuracy in clinical sample analysis. It is a good alternative to the single-label diagnostic methods.